Suppressing the non-switching contribution in BiFeO3-Bi4Ti3O12 based thin film composites to produce room-temperature multiferroic behavior. Issue 13 (October 2022) - Gumiel, C.; Jardiel, T.; Villalpando, A.P.; Lamotte, D.; Calatayud, D.G.; Calzada, M.L.; Jiménez, R.; García-Hernández, M.; Mompeán, F.J.; Caballero, A.C.; Villegas, M.; Peiteado, M.
Abstract: Exploiting the exceptional multiferroic characteristics of BiFeO3 -based systems depends largely on controlling the high leakage currents that often constrain the ferroelectric response of this material. This limiting circumstance is even more restrictive in the film geometry, where the high area/volume ratio can add complications related to the uncontrolled loss of a particularly volatile element such as bismuth. In this work we address the suppression of such non-switching contribution by preparing BFO-BiT thin film composites and using a low-temperature processing protocol in a fully aqueous medium. With an adequate and systematic doping of both oxides, the produced composites show both magnetic and ferroelectric response at room temperature, in a process that is also related to the fine matching between the two crystal lattices involved. The results obtained further indicate the possibility of applying a simple, sustainable protocol with high scalability prospects to fabricate exploitable multiferroic systems, i.e. with no need for large energy inputs nor sophisticated equipment.